2009
DOI: 10.1002/eji.200838232
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts from different sites may promote or inhibit recruitment of flowing lymphocytes by endothelial cells

Abstract: We examined the hypothesis that stromal fibroblasts modulate the ability of endothelial cells (EC) to recruit lymphocytes in a site-specific manner. PBL were perfused over HUVEC that had been cultured with fibroblasts isolated from the inflamed synovium or the skin of patients with rheumatoid arthritis or osteoarthritis, or from normal synovium, with or without exposure to the inflammatory cytokines TNF-α+IFN-γ. Fibroblasts from inflamed synovium, but no others, caused unstimulated HUVEC to bind flowing lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
165
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(182 citation statements)
references
References 49 publications
14
165
3
Order By: Relevance
“…In agreement with previous observations (7,8), we found that a function-blocking Ab against CXCR3 nearly abolished the adhesion of flowing PBL to TNF-and IFN-stimulated EC (Fig. 2A).…”
Section: Vascular Ec Stimulated With Tnf and Ifn Preferentially Recrusupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous observations (7,8), we found that a function-blocking Ab against CXCR3 nearly abolished the adhesion of flowing PBL to TNF-and IFN-stimulated EC (Fig. 2A).…”
Section: Vascular Ec Stimulated With Tnf and Ifn Preferentially Recrusupporting
confidence: 93%
“…There is also a strong presumption that chemokine signals are sufficient to promote lymphocyte migration over and through the endothelial monolayer and into inflamed tissue. In the case of EC treatment with TNF plus IFN, chemokines acting through the lymphocyte-borne receptor CXCR3 have been shown to stabilize attachment, but the signals inducing transendothelial migration have not been defined (7,8). Transendothelial migration of T cells has been observed within minutes of adhesion to EC activated with TNF (where blockade of b 2 integrins was inhibitory) (4), with TNF plus IFN (7), and for EC stimulated with TNF and to which stromal-derived factor-1a (CXCL12) or CCL19 (ELC) had been added to the EC surface (9).…”
mentioning
confidence: 99%
“…This molecule is regulated by other components of the ECM such as TSP1 and tumor necrosis factor-inducible gene 6 protein (TSG6) (60). These two proteins were presently observed to be up-regulated in stimulated NHDF, indicating that fibroblasts may be involved in regulating the recruitment of leukocytes by endothelial cells during inflammation, which was also observed by McGettrick et al (61). Such interrelations between angiogenesis and ECM reorganization as well as between fibroblasts and endothelial cells are further demonstrated by the interrelation of two important proteins mentioned before, PRRX1 and TNC.…”
Section: Discussionsupporting
confidence: 60%
“…The manner in which fibroblasts alter the adhesiveness of endothelial cells has been shown to be in part dependent upon the milieu from which the fibroblast was derived. For instance, rheumatoid arthritis-derived synovial fibroblasts increased adherence of lymphocytes to endothelial cells while those taken from uninflamed microenvironments (dermal fibroblasts) actually decreased adherence of lymphocytes [125]. Fibroblasts themselves express adhesion molecules with most expressing ICAM-1 particularly in the presence of T cells and with even greater levels of expression in the presence of activated T cells [113].…”
Section: Fibroblasts and Trafficking: Chemokines And Angiogenesismentioning
confidence: 99%